Pengembangan E-Modul Interaktif Sebagai Media Pembelajaran Pemrograman Siswa Kelas X SMKN 1 Unaaha di Daerah Tertinggal (3T) - Ibnu Haldun; Eko Marpanaji (Department of Electronics and Informatics Engineering Education, 2023)
Learning activities in schools located in disadvantaged areas (3T) can be said to be lagging when compared to schools in developed areas in Indonesia in terms of learning. Learning media that have not been developed at all and the use of ICT devices that have not been maximized in learning activities are one of the factors that the school is lagging in terms of learning. Therefore, this study aims to: (1) Produce interactive e-module teaching materials as programming learning media for class X TKJ SMK 1 Unaaha in the 3T area, (2) Determine the eligibility level of interactive E-Module for students in class X TKJ at SMKN 1 Unaaha. This study uses the research method (RnD) with the development model using the ADDIE model which includes several stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data collection techniques used in this study were: (1) Observation, (2) Interview, (3) Questionnaire/questionnaire). The test subjects were conducted on 33 class X TKJ students. The results showed that: Tests conducted by material experts obtained an average value of 3.5 with a very good product category, if converted into a percentage, the product yield was 87% with a very feasible product category. Tests by media experts produce a value of 3.8 with a very good product category, and if converted into a percentage, the result is 95%. Testing by users or students obtained an average result of 3.6 with the Very Good product category.